2020
DOI: 10.1007/s00455-020-10193-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Airflow Via High-Flow Nasal Cannula on Duration of Laryngeal Vestibule Closure

Abstract: The purpose of this experimental study was to investigate the influence of airflow via high-flow nasal cannula (HFNC) on the duration of laryngeal vestibule closure (dLVC) and Penetration-Aspiration Scale (PAS) scores. Twenty-nine healthy adults participated in a repeated-measures design. Each participant completed a videofluoroscopic swallow study while receiving airflow via HFNC across a control condition of zero flow and conditions of 10, 20, 30, 40, 50, and 60 L/min. Five raters rated dLVC and PAS scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Aspiration was not visualized, and increasing airflow was associated with increasing laryngeal vestibule closure. Although no association was objectively observed between penetration/aspiration at any flow rate, participants reported subjective complaints of increased difficulty swallowing at higher flow rates [35]. In another study with healthy volunteers, a flow rate > 40 L/min was associated with decreased swallowing function [36].…”
Section: Nutrition Via Oral Route In Patients With High-flow Nasal Cannulamentioning
confidence: 94%
“…Aspiration was not visualized, and increasing airflow was associated with increasing laryngeal vestibule closure. Although no association was objectively observed between penetration/aspiration at any flow rate, participants reported subjective complaints of increased difficulty swallowing at higher flow rates [35]. In another study with healthy volunteers, a flow rate > 40 L/min was associated with decreased swallowing function [36].…”
Section: Nutrition Via Oral Route In Patients With High-flow Nasal Cannulamentioning
confidence: 94%
“…However, prolonged apnea tolerance allows the laryngeal closure structure to remain closed until the end of swallowing, and aspiration is considered to have improved. This hypothesis may be supported by the fact that previous studies in healthy individuals have shown that HFNC oxygen therapy prolongs the laryngeal vestibule closure time during swallowing with increased oxygen flow [15] . Second, HFNC oxygen therapy may have improved the timing of swallowing.…”
Section: Discussionmentioning
confidence: 85%
“…Stimulation of receptors in the upper airway (soft palate, uvula, hard palate, faucial pillars, pharynx, and epiglottis) can initiate the swallowing reflex (Nishino, 2013;Nishino et al, 1989), so water infusion and light touch of catheter may have activated these receptors. Subsequent studies discussed later in this review (Allen & Galek, 2020;Flores et al, 2019) have also suggested that healthy adults may have the ability to cognitively engage and compensate to protect the airway when higher flow rates were deployed via HFNC.…”
Section: Discussion and Considerationsmentioning
confidence: 93%
“…This prospective design investigated the influence of airflow (LPM) delivered via HFNC on duration of laryngeal vestibule closure (dLVC) and described airway invasion during various LPM deliveries (Allen & Galek, 2020). Twenty-nine healthy adults were included.…”
Section: Methodsmentioning
confidence: 99%